1924
DOI: 10.1128/jb.9.6.559-579.1924
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Some Electrolytes on the Buffering Capacity of Bacterium Coli

Abstract: I. INTRODUCTION Studies which have been reported from this laboratory on the relation of hydrogen ion concentration to viability of Bact. coli (Winslow and Falk, 1923) have suggested the great importance of certain amphoteric reactions of the bacterial cell. The experiments recorded here were undertaken with the view of studying, from anothqr angle, certain anomalous results of the studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1926
1926
1951
1951

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…1. The earlier work of Shaughnessy and Falk (1924) has shown that cells of Bact. coli in the zone of physiological interest possess appreciable capacity to resist changes in reaction in such a manner as to avoid injury to the cell.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…1. The earlier work of Shaughnessy and Falk (1924) has shown that cells of Bact. coli in the zone of physiological interest possess appreciable capacity to resist changes in reaction in such a manner as to avoid injury to the cell.…”
Section: Discussionmentioning
confidence: 97%
“…In a previous communication from this laboratory (Shaughnessy and Falk, 1924) it was shown that the cells of Bact. coli exert a marked buffering effect when suspended in distilled water, an effect which rises to a maximum in the range favorable to viability (pH 6.0 to 6.9) and which gradually falls off with increasing acidity or alkalinity.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The concentrations of hydrogen ions were not the same in suspensions containing different neutral salts because different salts affect the buffering action of a bacterial suspension in different ways (Shaughnessy and Falk, 1924). Divalent cations prevented the production of alkaline substances more than monovalent cations, giving more acid suspensions.…”
Section: Data Obtained In Buffered Solutionsmentioning
confidence: 99%
“…We are not aware of any preceding researches on the viscosities of bacterial suspension. The experments reported here were undertaken to determine the influences of H-ion concentrations upon the viscosities of such suspensions, working with a strain of Bacterium coli which has been utilized in extensive studies on the effects of ions upon viability , upon the electrophoretic potentials of bacteria (Winslow, Falk and Caulfield, 1923;Winslow and Shaughnessy 1924) and upon the buffering properties of bacteria (Shaughnessy and Falk, 1924).…”
Section: Introduction and Theorymentioning
confidence: 99%